Respostas

2014-02-28T12:52:28-03:00
2x² - 5x - 3 = 0     a=2    b=-5    c=-3  
delta= b ao quadrado - 4.a.c
delta= (-5) ao quadrado - 4.2.(-3)
delta= +25 + 24
delta=49

-b mais ou menos raiz quadrada de 49, tudo sobre 2.a
-(-5) mais ou menos 7, tudo dividido por 2.2
5 mais ou menos 7, tudo dividido por 4
x'=5+7, tudo dividido por 4 = 3
x"=5-7, tudo dividido por 4 = -1/2
 
2014-02-28T13:24:40-03:00
Báskara.
2x²-5x-3=0          ====>a)2      b) -5      c) -3
Δ = (-5)² - 4.2.(-3)
Δ = 25 +24
Δ = 49

-b+-√Δ
   2.a
-(5)+-√49
  2.2
x1 = -5+7 = 2/4 = 1/2
         4
x2 = -5-7 = -12/4 = -3
         4
S = (1/2,-3)
É isso.
1 5 1